COMPARISON OF HIGH SENSITIVE C-REACTIVE PROTEIN LEVELS IN NEONATES DELIVERED BY DIFFERENT MODES OF DELIVERY - K.SOWMYA; C.M.PRABU KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Background: C-reactive protein (CRP) is a well-known indicator of inflammation, infection, and stress. Acute hypoxia that develops a short time before birth due to fetal distress may cause an elevation in the hs CRP levels. Hence this study was taken up to compare the hs CRP levels in neonates delivered by different modes of delivery and to determine if there are any changes due to fetal distress Materials and Methods: The present study included 34 full term neonates, delivered by vaginal route (10), elective caesarean (12) and emergency caesarean (12) sections in the Obstetrics Unit of Sri Ramachandra Medical College & Research Institute, Chennai. High sensitive CRP concentrations were measured in the venous cord blood of these neonates and analyzed in Dade Behring RXL Dimension clinical chemistry auto analyzer. Neonatal characteristics like gestational age, birth weight, Apgar scores, length and head circumference were also recorded . Statistical analysis was performed using the SPSS for Windows15.0 statistical program. The mean rank values were calculated and differences between mean values of the groups were analyzed by Kruskal Wallis Test and p values <0.05 were considered to be statistically significant. Pearson correlation analysis was used to determine the relationships between CRP levels and neonatal variables. Result: Statistically significant difference was observed in hs CRP levels in neonates delivered by different modes. No significant correlation was observed between CRP levels and other neonatal variables Conclusion: The babies delivered by elective cesarean section had significantly lower levels of hs CRP levels compared to babies delivered by other modes. Fetal distress in emergency cesarean section and vaginal delivery has lead to increased hs CRP levels. Thus increase in hs CRP levels reflects the intensity of stress on baby during delivery in the immediate postnatal period and does not necessarily indicate an infected status. Key words: hs CRP, delivery, fetal distress